2015
DOI: 10.1016/j.chembiol.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Flexibility of a Mutated Acyltransferase Domain and Implications for Polyketide Biosynthesis

Abstract: Polyketides are natural products frequently used for the treatment of various diseases, but their structural complexity hinders efficient derivatization. In this context, we recently introduced enzyme-directed mutasynthesis to incorporate non-native extender units into the biosynthesis of erythromycin. Modeling and mutagenesis studies led to the discovery of a variant of an acyltransferase domain in the erythromycin polyketide synthase capable of accepting a propargylated substrate. Here, we extend molecular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…The investigation initially intended to determine whether the activation via the synthetic SNAC could compete with the native CoA-activation in polyketide biosynthesis via the heterologous expression of MatB*. SNAC was used before in successful experiments to modify the biosynthesis of erythromycin in Sacchapolyspora erythraea and premonensin in S. cinnamonensis A495 Bravo-Rodriguez et al 2015).…”
Section: Feeding Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation initially intended to determine whether the activation via the synthetic SNAC could compete with the native CoA-activation in polyketide biosynthesis via the heterologous expression of MatB*. SNAC was used before in successful experiments to modify the biosynthesis of erythromycin in Sacchapolyspora erythraea and premonensin in S. cinnamonensis A495 Bravo-Rodriguez et al 2015).…”
Section: Feeding Experimentsmentioning
confidence: 99%
“…Engineering of AT for the derivatization of polyketide natural products is, thus, the subject of recent studies ( Fig. 1b) Bravo-Rodriguez et al 2015;Koryakina et al 2017). Several approaches to AT engineering are currently being discussed in the literature, ranging from reductionistic in vitro approaches using isolated enzymes to holistic in vivo experiments on whole assembly lines in natural producer organisms, typically Actinomycetes (Koryakina and Williams 2011;Klopries et al 2013;Koryakina et al 2013Koryakina et al , 2017Musiol-Kroll et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been several advances towards introduction of non-natural moieties using native AT promiscuity, 29,30 trans-ATs, 28,31,32,33 full AT swaps, 12 and AT active site mutagenesis. 14,15,16,17,18,25 Despite these advances, our lack of insight into the molecular and structural basis for substrate selectivity has meant targeting the same small number of AT residues without exploring the remainder of the ~430-residue domain or even the entire active site. Engineering selectivity between substrates often differing in only a single carbon unit without a defined binding pocket is a unique protein engineering challenge.…”
Section: Discussionmentioning
confidence: 99%
“…8,13 In contrast to exchanging residues between ATs, point mutations in or near the YASH motif of ATs of the DEBS (EryAT6) or pikromycin (PikAT5/PikAT6) pathways enable incorporation of non-natural extender units and significant changes to substrate selectivity without the deleterious effects of domain/module swapping. 14,15,16,17,18 Yet, not all of these first-generation mutations are transferable between ATs in different PKSs. 18 To be maximally efficient and broadly applicable, motif-swapping and point mutagenesis would benefit from a comprehensive inventory of AT residues responsible for substrate selection.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the type I modular PKSs are an especially attractive target for engineering because their organization and structure lends itself to connecting sequence with product structure (1,2,6). Previous studies have shown that the acyltransferase (AT) domain within the PKS (cis-AT) is essential to determining extender unit identity and can be engineered to enable insertion of alternative extender units (7)(8)(9). Alternatively, the intrinsic selectivity of the cis-AT can be bypassed by inactivation and complementation with a standalone AT enzyme (trans-AT) as another approach to introducing nonnative substituents (10)(11)(12).…”
mentioning
confidence: 99%